Effect Of Combination Administration Of Leaf Extract Star Fruit (Averrhoa Bilimbi L.) and Ginger Rhizome Red (Zingiber Officinale var. Rubrum) Until Against Creatinine In Mice (Mus Musculus) CCl4 Induced and Its Utilization As A Learning Medium - Rahayu, Ratna Dwi; Ramadhan, Achmad; Sutrisnawati (Universitas Islam Riau (UIR) Press, 2026)
The combination of starfruit (Averrhoa carambola) and red ginger (Zingiber officinale var. rubrum) is important to investigate because both plants contain bioactive compounds with antioxidant potential. Starfruit contains vitamin C and phenolic compounds, while red ginger contains gingerol and other antioxidant compounds that may support physiological functions and help prevent disease. Therefore, this combination has potential as a natural antioxidant source. This study aims to understand the combined effects of starfruit leaf extract and red ginger rhizome on creatinine levels in mice that have been given CCl4 treatment. The method used is a laboratory experiment with a Completely Randomized Design (CRD) design consisting of 24 mice divided into 6 groups and 4 experimental replications. The normal control group (Kn) is a group that is only given food and water, the negative control group (K-) is given CCl4 induction, groups P1, P2, P3 and P4 are given CCl4 induction and a combination of starfruit leaf extract and red ginger rhizome with concentrations of 20%, 40%, 60% and 80%. Data were analyzed by ANOVA statistical test via SPSS version-26. The results of the study showed that the combination of starfruit leaf extract and red ginger rhizome significantly reduced creatinine levels in mice induced by CCl4, with an effective concentration of 80%. The learning media applied in this study, a flipbook e-module, met the very good category as a learning medium.